Identifying Knowledge and Practices regarding Cancer Patient Malnutrition: A Survey Study among Oncologists. (30th June 2022) - Sonmez, Ozlem; Tezcanli, Evrim; Bas, Dilsat; Kazanci, Hande Busra; Altinok, Ayse; Demir, Atakan; Uluc, Basak Oyan
Abstract: Malnutrition is one of the most common complications of cancer and its treatments with a prevalence of up to 80% among cancer patients. Thus, standardized and target-oriented attitudes of oncologists toward nutritional management are particularly important. This study aims to report the questionnaire-based evaluation of different views toward medical nutrition among medical and radiation oncologists with the purpose to underline the problems and requirements of cancer nutrition. A national web-based survey composed of 26 multiple choice questions about participant demographics, level of knowledge about cancer nutrition, and approaches to malnutrition were completed by 247 oncologists. The survey was answered by a total of 247 (34%) radiation and medical oncologists. The majority of the oncologists (77%) were working at the University Hospitals and Education & Research Hospitals. Most of them were specialists with 5-10 years of experience. Nutritional status was routinely assessed in oncology units of 84% of (206) oncologists. However, only 50% reported nutritional evaluation follow-ups without waiting for a patient's declaration and 5 (2%) oncologists reported the absence of nutritional evaluation in their unit. Additionally, more than 79% of participants reported that their knowledge was not enough about enteral and parenteral nutrition while 8% were skeptical about the benefits of medical nutrition. Although the role of nutrition as an essential part of cancer care is widely recognized, the availability of limited high-quality evidence, problems of accessibility, lack of routine nutritional evaluation, and varying indicators for malnutrition are some of the problems preventing standardized nutritional management. Therefore, there are a variety of approaches and barriers to the implementation of guidelines. Further studies are needed to identify areas of improvement, as well as strategies to implement nutritional therapy in cancer care.